Trying to teach dialogically: The good, the bad, and the misguided. (November 2019) - Shea, David P.
The goal of dialogic teaching is to position students as active participants who engage in academically accountable talk, but research consistently suggests that a major stumbling block is the teacher's own interactional style. To explore the issue from an emic perspective, I carried out an action research investigation of advanced proficiency classes for English as a foreign language (EFL) that I taught on the university level in Japan. Data included audiotaped recordings of teacher-fronted whole-class discussions that were analysed qualitatively. I found that the effort to teach dialogically was somewhat successful, but missteps and misguided assumptions about effective instructional strategies were also evident. Findings point to both the complexities of orchestrating active engagement of reticent students within the third space of the second language (L2) classroom, and the critical role of teacher authority to elicit and coordinate student engagement.